Resurrecting Shakespeare's Ghost Plays. (4th September 2018) - Reid, Lindsay Ann
Abstract: This article draws attention to a group of remarkably similar novels published between 2003 and 2009: William Martin's Harvard Yard, Jennifer Lee Carrell's The Shakespeare Secret (also known as Interred with Their Bones ), Jean Rae Baxter's Looking for Cardenio, and A. J. Hartley's What Time Devours . Each of these mysteries portrays a para-academic protagonist's literary quest to rediscover one of Shakespeare's so-called 'ghost plays' – that is, either Love's Labour's Won or Cardenio. This article seeks, first, to locate these novels' imaginative treatments of lost Shakespearean works in relation to academic trends and ideas about these two plays. It then turns its attention to codifying and analysing the common characteristics of this microgenre. In so doing, it highlights how this group of novels is conspicuously infused with the imagery and discourses of spectrality: these texts recurrently redeploy metaphors of haunting, liminality, and ephemerality to portray the mechanics and significance of Shakespearean literary discovery.